Uma união “instável”? A nova lei de abuso de autoridade como possível incidente da disputa política entre os poderes legislativo e judiciário - Real, Isadora de Almeida (2021)
This paper aims to examine the particular political dispute between the Federal Parliament and the Organs of the Brazilian judicial system, based on the analysis of the new Law of Abuse of Authority. At two different times in national political life, laws were passed with the scope of disciplining authorities' abuses in Brazil: in the second year of the Military Regime (Law No. 4,898, of December 9, 1965) and in 2019 (Law No. 13,869, of 05 Sep.2019), 31 years after the promulgation of the 1988 Constitution. Considering the two distinct contexts – the first, of an authoritarian nature; the second, of a democratic nature –, it is deduced that the relationship between the Powers is different: prevalence of the Executive Power in the first case; of the Legislative, in the second. With an analytical-descriptive approach, the purpose of this work will be to demonstrate, from the review of the law, that there was a political judgment in its surroundings. The main conclusion was that the Legislative Branch, ultimately – given the relationship between the branches – took advantage in terms of the prevalence of its interests.